SEMI-FINISHED PRODUCT TECHNOLOGY FOR FROZEN DESSERTS - Слащева, Аліна (Modern engineering and innovative technologies, 2023)
The analysis of literary sources showed that the creation of products with reduced glycemic load and functional properties are new ways of improving the technologies of ice cream and frozen desserts. It has been proven that lowering the glycemic index is